Economic Costs Associated with Motorbike Accidents in Kathmandu, Nepal - Sapkota, Diksha; Bista, Bihungum; Adhikari, Shiva Raj (Frontiers in Public Health, 2016)
Background: Road traffic accidents, considered as global tragedies, are in increasing trend however, the safety situation is very severe in developing countries incurring substantial amount of human, economic and social costs. Motorcycle crashes, the commonest form, occur mostly on economically active population. However, there is limited coverage of studies on economic burden of motorcycle crashes. This study aims to estimate the total cost and DALYs lost due to motorbike accidents among victims of Kathmandu Valley. Materials and Methods: Retrospective cross-sectional study was conducted among the patients having history of motorbike accidents within past twelve months and at least 3 months from the date of data collection. Interview was conducted using proforma among 100 victims of accidents and their care giver in case of death from November 15, 2014 to May 15, 2015. Cost estimation of motorbike accident was done based on human capital approach. Data collection tool was pretested and collected data were analyzed by SPSS and Microsoft excel. Results: Males (79%) belonging to the economically productive age group shared the highest proportion among total accidents victims. Most common reason for accidents was reported to be poor road condition (41%). Indirect cost was found to be significantly higher than direct costs highlighting its negative impact on economy of family and nation due to productivity loss. Total Disability Adjusted Life Years (DALYs) lost per person was found to be 490 years and national estimation showed large burden of motorbike accidents due to huge DALY loss. Conclusions: For low resource countries like Nepal, high economic costs of motorbike accidents can pose additional burden to the fragile health system. These accidents can be prevented, and their consequences can be alleviated. There is an urgent need for reinforcement of appropriate interventions and legislation to decrease the magnitude of it and its associated grave economic consequences so as to nib this emerging epidemic in the bud.